Hubungan Antara Self Efficacy dengan Komunikasi Asertif pada Mahasiswa Psikologi (SUKMA : Jurnal Penelitian Psikologi, 2020)
The study aims to know the relationship between self efficacy with the assertive communication on the student psychology hypothesis filed in this study is as follows there is a positive relationship between self efficacy with communication Assertive on psychology students, the higher the self efficacy then the higher the assertive communication. The sample in this study is the University faculty student Psychology 17 August 1945. Sampling techniques in this study probability sampling simple random sampling. The measuring instrument in this study uses the self’ efficacy scale and the asertif communication scale. The data analysis technique used in this study was the correlation technique of Product Moment Pearson. Data analysis calculation results show a very significant positive correlation between self efficacy and asertif communication. The higher the self efficacy then the higher the asertif communication. Similarly, the lower the self efficacy then the lower the asertif communication. From the results of the analysis the data indicates that the hypothesis is declared  acceptable. Keywords: Asertif Communication; Self-efficacy; Student  Penelitian ini bertujuan untuk mengetahui hubungan antara self efficacy dengan komunikasi asertif pada mahasiswa psikologi hipotesis yang diajukan dalam penelitian ini adalah sebagai berikut ada hubungan positif antara self efficacy dengan komunikasi asertif pada mahasiswa psikologi, semakin tinggi self efficacy maka semakin tinggi komunikasi asertif. Sampel dalam penelitian ini adalah mahasiswa fakultas psikologi universitas 17 Agustus 1945. Teknik pengambilan sampel dalam penelitian ini probability sampling yaitu simple random sampling. Alat ukur dalam penelitian ini menggunakan skala self efficacy dan skala komunikasi asertif. Teknik analisis data digunakan dalam penelitian ini adalah teknik korelasi Product Moment Pearson. Hasil perhitungan analisis data menunjukkan terdapat korelasi positif yang sangat signifikan antara self efficacy dengan komunikasi asertif. Semakin tinggi self efficacy maka semakin tinggi pula komunikasi asertif. Begitu pula sebaliknya semakin rendah self efficacy maka semakin rendah pula komunikasi asertif. Dari hasil analisis data tersebut menunjukkan bahwa hipotesis dinyatakan diterima. Kata Kunci : Komunikasi Asertif; Efikasi Diri; Siswa